2015
DOI: 10.1186/s12889-015-2652-y
|View full text |Cite
|
Sign up to set email alerts
|

Contraceptive use before first pregnancy by women in India (2005–2006): determinants and differentials

Abstract: BackgroundThere exist ample of research literature investigating the various facet of contraceptive use behaviors in India but the use of contraception by married Indian women, prior to having their first pregnancy has been neglected so far. This study attempts to identify the socio demographic determinants and differentials of contraceptive use or non use by a woman in India, before she proceeds to have her first child. The analysis was done using data from the third National Family Health Survey (2005–2006),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

12
33
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(47 citation statements)
references
References 12 publications
12
33
0
2
Order By: Relevance
“…The current study reported that 15.9% of married women below 19 years of age and a higher proportion of tribal women were desirous to become pregnant more than non-tribal women (p < 0.001). This age distribution was similar to population-based studies done in other parts of India and South Asia [9][10][11][12][13]. The educational opportunities and better socioeconomic status in non-tribal areas might be a reason for this difference.…”
Section: Discussionsupporting
confidence: 86%
“…The current study reported that 15.9% of married women below 19 years of age and a higher proportion of tribal women were desirous to become pregnant more than non-tribal women (p < 0.001). This age distribution was similar to population-based studies done in other parts of India and South Asia [9][10][11][12][13]. The educational opportunities and better socioeconomic status in non-tribal areas might be a reason for this difference.…”
Section: Discussionsupporting
confidence: 86%
“…Our results also highlight not only the importance of women's education with regard to their fertility preferences, but also the education level of their partners. Studies conducted in India have found that the woman's education level is associated with delaying the first pregnancy, but also with actual contraceptive use to delay it [23,24]. A multi-country study on partner's education did not specifically find associations with delaying the first pregnancy; however, associations with increased contraceptive use as well as other healthy reproductive behaviours were found [31].…”
Section: Discussionmentioning
confidence: 95%
“…Previous studies have assessed the methodological limitations of intimate partner violence studies. Asserting control over their wives is common for aggressors, and thus a large proportion of abused women might be excluded from surveys such as the DHS, which leads to underestimation of the true problem [23]. While the response rate for the IPV module was 95%, we lack data on the characteristics of those who refused to participate.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations